Application of Audio Frequency Magnetotelluric (AMT) Method for Nickel Mineral Exploration in Area Laeya District, South Konawe Regency, Southeast Sulawesi Province, Indonesia - Hasria; P. Ramba, Jeremy Patrio; Safani, Jamhir; Arisona; Junursyah, G.M. Lucki (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
The AMT (Audio Frequency Magnetotelluric) method is a geophysical method that uses natural sources (passive method) so it does not require artificial sources and is very effective in mapping the resistivity contrast of subsurface rocks. The AMT (Audio Frequency Magnetotelluric) method is a geophysical method that uses natural sources (passive method) so it does not require artificial sources and is very effective in mapping the contrast of subsurface rock resistivity. This study aims to determine the coherence and nickel mineralization zones in the Laeya District area, South Konawe Regency, Southeast Sulawesi Province using the AMT method and supported by using drill data. The coherence of AMT data in the Laeya District area, South Konawe Regency based on the magnitude and phase curves of apparent resistivity after the XPR selection process experienced a significant increase in data quality at all points indicated at point LY02 from 49.09% coherence to 78.32%. Nickel mineralization zone based on 2D cross-section data of AMT resistivity and Drilling data in Laeya District, South Konawe Regency shows the distribution of nickel enrichment areas which are qualitatively marked by light blue color with resistivity values of 11 to 21 Ohm m located at points LY03, LY04, LY06, LY07 and LY08. Drilling data shows the presence of limonite layers at drill points DHB15 and DHB16. The presence of Sulawesi Molasa which is a feature of nickel deposits in the South Konawe area is also detected in the 2D cross-section.